Peran Serta Fakultas Kesehatan Terhadap Pemberian Edukasi dan Pelaksanaan Skrining Tumbuh Kembang Bayi, Balita, dan APRAS di Posyandu Desa Randu Merak - Harwin Holilah Desyanti; Ummu Humairah; Amilya Maika Fitriani; Devi Merlinda; Rika Wulandari; Nurul Qomariyah (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
Providing education to the community about the importance of growth and development screening of infants, toddlers and APRAS is very useful for mothers and health cadres. Where mothers or cadres can detect early developmental deviations in children in their growing age. The purpose of this community service is to provide education about the importance of early detection of growth and development and screening to determine whether the growth and development of children is in accordance with age. The implementation of this education uses leaflets and teaching sheets and growth and development screening using KMS and KPSP which is one of the instruments to determine the normal or deviant growth and development of children. The number of counseling participants was 29 people (20 parents and 9 cadres) while the number of screening participants was 20 people. After being given education to mothers and cadres, it is very helpful for mothers and cadres to increase their knowledge and get the results of screening 20 normal children according to age.